2022
DOI: 10.1039/d2lc00331g
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of the growth behavior of perovskite CsPbBr3 nanocrystals in a microfluidic system

Abstract: Understanding the growth behavior of nanoparticles and semiconductor nanocrystals under dynamic environments is of profound importance in controlling the sizes and uniformity of the prepared nanoparticles and semiconductor nanocrystals. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…This phenomenon occurs when the size of NCs increases as the reaction time progresses, resulting in a shift of the excitonic emission peak towards longer wavelength. 29,45 The as-prepared NCs synthesized by fluidic channel reaction or hot injection were compared in subsequent experiments. TEM showed that all of the NCs were of cubic shape, and the NCs prepared by fluidic channel reaction showed a larger size (15 AE 2 nm), compared with that by hot injection (10 AE 2 nm) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon occurs when the size of NCs increases as the reaction time progresses, resulting in a shift of the excitonic emission peak towards longer wavelength. 29,45 The as-prepared NCs synthesized by fluidic channel reaction or hot injection were compared in subsequent experiments. TEM showed that all of the NCs were of cubic shape, and the NCs prepared by fluidic channel reaction showed a larger size (15 AE 2 nm), compared with that by hot injection (10 AE 2 nm) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PL characteristics have been widely used for in situ monitoring and analyzing the growth of PNCs because of their size dependent bandgap/PL peak. 43–45 Fig. 2(a) and (b) show the temporal evolution of the PL peak and FWHM of the PNCs synthesized in ODE, toluene, and MMA, and the corresponding spectra are provided in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PL characteristics have been widely used for in situ monitoring and analyzing the growth of PNCs because of their size dependent bandgap/PL peak. [43][44][45] Fig. 2 precursor diffusion in the solution, causing the limited nucleation and growth rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microfluidics has been demonstrated to be a reliable and powerful technique for large-scale manufacturing of nanoparticles and nanocrystals. [14][15][16] Compared with the small-scale synthesis of materials for fundamental research, microfluidics can provide continuous fabrication of materials and eliminate the samples' irreproducibility originating from batch-to-batch fabrication. [17][18][19] Currently, microfluidics is used to synthesize Pb-based NCs.…”
Section: Introductionmentioning
confidence: 99%